Development of an IoT-Based Tidal Gauge With Ultrasonic Sensors - Alajuri, M Hasbi Sidqi; Kusuma, Hollanda Arief; Bavitra, Bavitra; Harahap, Basyaruddin Ismail (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Tides are the periodic rise and fall of sea levels caused by the gravitational effects of the moon and the sun. This tidal phenomenon can be measured manually or automatically using instruments. The objective of this study is to design and develop a tide gauge instrument using the JSN-SR04T sensor based on the Internet of Things (IoT). The research method includes hardware design, electrical design, firmware development, and dashboard creation. Once the system design is completed, the components are assembled. Functional and laboratory tests are conducted to ensure that each component operates properly, followed by field testing. The tide gauge instrument is capable of operating for 7 days with good accuracy in the measurement range of 25 cm to 200 cm (with an error between 0.02 and 0.16 cm). Field observations indicate that the type of tide corresponds to previous studies, which is a mixed tide. The DS18B20 sensor produced temperature readings that matched those of a standard thermometer.Pasang surut merupakan gerak naik turun muka air laut secara periodik yang disebabkan oleh efek gravitasi bulan dan matahari. Fenomena pasang surut ini bisa diukur secara manual dan otomatis menggunakan instrumen. Tujuan penelitian ini yaitu membuat rancang bangun instrumen pengukur pasang surut dengan sensor JSN-SR04T berbasis IoT. Metode penelitian dimulai dari perancangan hardware, perancangan electrical, perancangan firmware, dan perancangan dashboard. Setelah perancangan sistem selesai maka dilakukan perakitan komponen. Uji fungsionalitas dan uji laboratorium dilakukan untuk memastikan setiap komponen berfungsi dengan baik. selanjutnya, diakukan uji lapangan. Instrumen pasang surut ini dapat bekerja selama 7 hari dengan akurasi yang baik pada rentang pengukuran 25 cm hingga 200 cm (Error 0.02 hingga 0.16). Berdasarkan hasil pengamatan di lapangan menunjukkan bahwa jenis pasang surut sesuai dengan peneliti sebelumnya yaitu campuran. Hasil pengukuran sensor DS18B20 memiliki nilai suhu yang sama dengan pengukuran termometer.